2006
DOI: 10.1093/europace/eul064
|View full text |Cite
|
Sign up to set email alerts
|

Junctional rhythm quantity and duration during slow pathway radiofrequency ablation in patients with atrioventricular nodal re-entry supraventricular tachycardia

Abstract: The amount and duration of accelerated junctional rhythm is correlated with the total abolishment abolition of slow pathway conduction. A higher amount and duration of accelerated junctional rhythm during radiofrequency applications may be an additional marker of successful ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
(32 reference statements)
0
17
2
Order By: Relevance
“…Several investigators have reported persistent junctional rhythm after RF ablation of the slow AV nodal pathway to be a highly predictive measure of successful ablation, reflecting more intense injury from the RF ablation on the peri-AV nodal tissue. [20][21][22] Junctional tachycardia can last seconds to more than 1 hour after RF ablation. 18 Although it is unclear, PO JET might have its origin from the slow AV nodal pathway; thus, to facilitate PO JET, we attempted physical injury (RF ablation and tricuspid valve stretch) to this heart region.…”
Section: Physical Injury To the Csmentioning
confidence: 99%
“…Several investigators have reported persistent junctional rhythm after RF ablation of the slow AV nodal pathway to be a highly predictive measure of successful ablation, reflecting more intense injury from the RF ablation on the peri-AV nodal tissue. [20][21][22] Junctional tachycardia can last seconds to more than 1 hour after RF ablation. 18 Although it is unclear, PO JET might have its origin from the slow AV nodal pathway; thus, to facilitate PO JET, we attempted physical injury (RF ablation and tricuspid valve stretch) to this heart region.…”
Section: Physical Injury To the Csmentioning
confidence: 99%
“…Iakobishvili et al (24) reported the cycle length of accelerated junctional rhythm during RF ablation of slow pathway was variable, and Chinushi et al (7) reported that the appearance followed by a slowing and/or disappearance of repetitive ventricular responses during RF application was consistent with successful RF ablation in RVOT VT. We experienced the similar responses in our cases, so a slowing and/or disappearance of repetitive ventricular response during RF application might be another marker of successful ablation, but we need further studies with a larger number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study conducted by Iakobishvili et al. [ 11 ] found that the higher amount and longer duration of junctional rhythm are correlated with complete SP elimination. The differences of the periprocedural parameters indicated that AVNRT characteristics and electrophysiological profile in patients with SP elimination might differ from that of the patients in whom only SP modification was achieved.…”
Section: Discussionmentioning
confidence: 99%